(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the concept of “Enlightened Generation” and ways of educating an enlightened generation, as well as the fact that the concept of “Enlightened Generation” reflects the community of the generation of a given era with its concentration on the essence of this concept which plays an important role in the systematic implementation of changes in society, and this will be analyzed from a socio-philosophical point of view.The article also shows five characteristics of the famous philosopher, scientist, academician S. Shermuhammedov, aimed at finding solutions to the problems of education and upbringing of the enlightened generation. At the same time, the opinions of Yusuf Khos Hajib and Abdullah Avloni about the “Enlightened Generation” will be covered in details.